Breast cancer knowledge and awareness among non-health sciences university students in Puncak Alam / Noor Syamira Mokhtar, Nurul Ellyna Mohd Noh and Nur Fatin Fatihah Ngah - Mokhtar, Noor Syamira; Mohd Noh, Nurul Ellyna; Ngah, Nur Fatin Fatihah (2016)
Background: High breast cancer mortality rate in Malaysia was contributed from the lacking of breast cancer knowledge and awareness which often lead to late diagnosis of the disease. Little known about the level of knowledge and awareness of breast cancer in Malaysia especially among Non-Health Sciences university students as they will become high risk group in the future. Thus, this study was conducted to assess the level of knowledge and awareness of breast cancer among Non-Health Sciences student in UiTM Puncak Alam, Selangor Campus. Objective: To determine the level of knowledge and awareness of breast cancer among non-health programme university students. Methods: A cross-sectional survey was conducted to non-health sciences university students using self-administered questionairre to investigate breast cancer knowledge and awareness among them. Total number of participants completed this survey were 367 students. Result: The result showed average knowledge of breast cancer among university student in UiTM Puncak Alam. Most of the participants were not aware that alcohol consumption, mammograms, oral contraceptives and being overweight can increase risk of breast cancer. For awareness of breast cancer, most of the participants have poor level of breast cancer awareness. They do not know that the changes in the colour or shape of a woman's nipple could be a sign of breast cancer.